Research on the efficiency optimization of food reserve under the complementary reserve mode of government and enterprise in China - Jiang, Qijun; Ji, Xiaoyang (Frontiers in Sustainable Food Systems, 2024)
Food reserve is the cornerstone of national strategic security. China strives to build a complementary reserve system between government and enterprises, and how to improve the efficiency of food reserves is a matter of great concern to the government and society. Based on the analysis of the connotation of food reserve efficiency, this paper constructs the revenue function and the cost function of food reserve in an emergency and uses the cost–benefit method to explore the best ratio of government reserve, corporate social responsibility reserve, and commercial inventory when maximizing the efficiency of food reserve. This ratio is closely related to the total food reserve, the scale of supply interruption, the reserve cost of food stored by enterprises, and the government’s subsidy cost for the social responsibility reserve. The unit subsidy cost of government to social responsibility reserve is inversely proportional to the proportion of corporate social responsibility reserve to corporate reserve. Doing a good job in the social responsibility management of food enterprises is an effective way to improve the efficiency of food reserves. To expand the scale of social responsibility reserves and realize “storing food in enterprises,” the subsidies given by the government for corporate social responsibility reserves should not be too high. Taking food social responsibility reserve as an important part of corporate social responsibility, it’s the key to promoting enterprises to actively undertake food social responsibility reserves. The conclusion of this paper provides a theoretical basis and decision-making reference for how to improve the efficiency of food reserves.